Aplicabilidad del parágrafo 57 de la ley 1453 de 2011 (2013)
The applicabilityof the paragraph ofArt.301 ofC.P.P.Amended by art.57 of Act1453of 2011, which cut intoquarterprofitwhen the captureoccurred inflagrancystate, brokereward systemthe principles of justice, equality rights, due process, the legal security ofthe accused, violating the guaranteeslack ofunity of purpose, defining theregulatoryprovisionfavoring thecriminal whoraidedlater inthe hearingofcomplaint, so the legislatureshouldadoptthe same rebatetoallprocedural stages, changingarts.356paragraph 5and 367Inc. Enshriningtworebates forthe start of thepreliminary hearingandtrial.TheSupreme Courtand the Constitutional Courtdeclaredenforceablestandard, whereas thedecrease of aquarter ofpunitivebenefitwas extended toallprocedural opportunitieswherecaught in flagrancymayacquiesceto fees andsign agreements withtheAttorney General'sNation.